2017
DOI: 10.15547/bjvm.986
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different levels of propolis in diets on performance, gastrointestinal morphology and some blood parameters in broiler chickens

Abstract: SummaryShaddel-Tili, A., B. Eshratkhan, H. Kouzehgari & M. Ghasemi-Sadabadi, 2017. The effect of different levels of propolis in diets on performance, gastrointestinal morphology and some blood parameters in broiler chickens. Bulg. J. Vet. Med., 20, No 3,[215][216][217][218][219][220][221][222][223][224] A study was conducted to determine the effect of different levels of propolis in diets on performance, carcass characteristics, gastrointestinal morphology and some blood parameters in broiler chickens. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 20 publications
3
16
0
6
Order By: Relevance
“…10, 0. 15, 0.20, 0.25, 0.5, 1.5 and 2.0 g/kg diet (Shalmany & Shivazad, 2006;Shaddel-Tili et al, 2016). Similar results have been reported in other poultry species.…”
Section: Broilers Performancesupporting
confidence: 85%
See 1 more Smart Citation
“…10, 0. 15, 0.20, 0.25, 0.5, 1.5 and 2.0 g/kg diet (Shalmany & Shivazad, 2006;Shaddel-Tili et al, 2016). Similar results have been reported in other poultry species.…”
Section: Broilers Performancesupporting
confidence: 85%
“…Similarly, Çetin et al (2010) documented a slight increase in haematocrit and haemoglobin values in laying hens receiving 3.0 g/kg of propolis. In broiler chicken, packed cell volume and heterophil counts significantly increased at a dose of 2.0 g propolis/kg diet (Shaddel-Tili et al, 2016). Abdel-Rahman & Mosaad (2013) found that ducks fed propolis diets had much higher haemoglobin con-centrations than the control, but the packed cell volume was not affected.…”
Section: Effect Of Propolis On Intestinal Microfloramentioning
confidence: 99%
“…Flavonoids are one of the components which are known to be responsible for the biological activities of propolis (Galal et al 2008). Propolis may exert multiple positive effects on human and animal health (Shaddel-Tili et al 2017). Besides, immunomodulatory effects of propolis have been determined (Burdock 1998).…”
Section: Production Performancementioning
confidence: 99%
“…The process of absorption that occurs in the body of the livestock is influenced by the age, so that the feed given to livestock should be adjusted to the age of the livestock. The use of different feed ingredients with certain treatments causes differences in body weight gain in broiler chickens (Shaddel-Tili et al, 2016).…”
Section: Body Weight Gainmentioning
confidence: 99%